Development of techniques for quantitative analysis of lime flowers - Demyanenko, D; Demyanenko, V; Breusova, S (Annals of Mechnikov’s Institute, 2020)
Introduction. The article is devoted to the development of techniques for quantitative analysis of lime flower in order to make amendments to existing pharmacopoeian monographs for this herbal drug. Lime inflorescences contain lipophilic biologically active substances (BAS) causing notable antimicrobial and anti-inflammatory effects and also more polar phenolic compounds with antiulcer activity. Considering this, it’s necessary to regulate all these groups of BAS quantitatively. Materials and methods. For this study six batches of lime flowers harvested in 2008-2009 yrs. in Kharkiv, Rivno and Zhitomir regions were used as crude herbal drug. Loss on drying was determined by routine pharmacopoeian procedures. Total content of lipophilic substances was determined gravimetrically after Soxhlet extraction of samples 1, 5, 7 and 10 g in weight with methylene chloride, considering that by its extracting ability this solvent is close to liquefied difluorochloromethane (freon R22) used by us for obtaining of lipophilic complexes. The duration of complete analytical extraction was determined by infusion of six 10 g assays of lime flowers during 1, 2, 3, 4, 5, 6 hours, then quantity of lipophilic extractives was revealed gravimetrically. Quantity of essential oil in lime flowers was evaluated under the procedure of ЕР7, 2.8.12. Weight of the herbal drug sample was 200 g, distillation rate – 2,5- 3,5 ml/min, volume of distillation liquid (water) – 500 ml, volume of xylene in the graduated tube – 0,50 ml.Total flavonoid content recalculated to quercetin was determined after hydrolysis with acidified acetone, withdrawing of flavonoid aglycones with ethylacetate and by further spectrophotometry of their complexes with aluminium chloride. All quantitative determinations were replicated five times for each assay. All chemicals and reagents were of analytical grade. Results and discussion. It was found that adequate accuracy of the analysis of lipophilic extractives taken with methylene chloride was achieved if assay weight is not less than 7 g: relative error was less than 2 %. Study of extraction kinetics showed that after 4 hours lipophilic substances soluble in methylene chloride were taken almost completely. Analyzing 6 batches of lime flowers from different Ukrainian regions, it was found that yield of total extractives taken with methylene chloride did fall within insignificant limits – 1,86-2,26 %, that testifies onto rather stable accumulation of these biologically active substances in lime flowers even despite different climatic conditions. Essential oil content varied in rather wide limits – 0,34-0,55 ml/kg of herbal drug and considerably depended on harvest place: in the batches from Northwest of Ukraine this value was less than in the Eastern ones. Year of harvesting had less influence on quantity of essential oil in lime flowers. The relative error of the quantitative determinations was within 4–8 %.Total flavonoid content in the analyzed batches of lime flowers was considerably variable (from 0,30 to 0,52 %) and depended mainly on place of harvesting, and this crude herbal drug from the north-west of Ukraine (Rivno region) showed the highest results among the analyzed samples. Besides, if consider the lower limit regulated by the monograph of Belarusian Pharmacopoeia, p. 370, then only one batch conformed to the norm (not less than 0,5 %). Therefore it’s recommended to fix the lower limit 0,3 % for content of total flavonoids in the corresponding monograph draft or analytical normative documentation. The relative error of the quantitative determinations of flavonoids was within 1,5–3,1 %.Conclusion.Six batchesof lime flowers harvested in various regions of Ukraine in 2008 and 2009 yrs. were investigated. Based on the results obtained it is offered to regulate the following quantity parameters in the amended monograph draft for lime flower: total extractives taken with methylene chloride – not less than 1,8 %, essential oil content – not less than 0,3 ml/kg, total flavonoid content recalculated as quercetin - not less than 0,3 %.